Observations of geophone spurious resonance. Issue 1 (1st December 2019) - Hearn, Steve; Strong, Shaun; Kinmont, Andrew
Summary: A detailed understanding of the frequency response of geophones is critical for the design and quality control of broadband seismic surveys. We illustrate a pragmatic methodology for accurate identification of geophone spurious resonances. We include tap-test examples from conventional 10 Hz geophones, and from 5 Hz and 10 Hz high-output nodal sensors. High-frequency noise sources, including high-voltage harmonics can interfere with the accurate identification of the spurious events. This problem can be overcome by subtraction of matched noise spectra